Differential resource selection within shared habitat types across spatial scales in sympatric toads - Lukas Indermaur; Thomas Winzeler; Benedikt R. Schmidt; Klement Tockner; Michael Schaub (Ecology, 2009)
Differential habitat selection is a central component in the evolution of species, but it has been quantified rarely for sympatric species in relation to the multiple impacts of resources at the spatial scales at which animals operate. Our main goal was to quantify the selection of terrestrial summer habitats in a natural floodplain in Italy by two sympatric amphibians ( Bufo bufo spinosus and B. viridis ) as a function of habitat type, prey density, and temperature. We applied a Bayesian resource selection model at three spatial scales: (1) home range placement within the floodplain, (2) space use within 95% home ranges, and (3) space use within 50% core areas. Using these data we explored whether processes acting at large scales lead to space use patterns at small scales and whether the two species use the same habitat types in a way that would facilitate coexistence. Habitat selection was determined by habitat type, prey density, and temperature at all spatial scales, resulting in slightly higher prey density and significantly lower temperature within than outside home ranges. We conclude that amphibians perceive the distribution of habitat types as well as gradients in prey density and temperature at all spatial scales. The effects of habitat type dominated home range placement while prey density and temperature most strongly affected space use within home ranges. Our results suggest that home range placement relies on broad habitat features that indicate resource availability at small spatial scales. At the smallest spatial scale, the selection of prey and refugia is most probably facilitated due to the accumulation of environmental information as animals may sample the entire area. Both species largely preferred the same habitat types, but used them differently in relation to resources across the three spatial scales. For example, while one species used the same habitat type for foraging, the other used it for resting or both resting and foraging. Niche differentiation through differential resource selection within shared habitat types at all spatial scales may therefore facilitate the coexistence of the two species in terrestrial summer habitats.